A multicenter retrospective study on anesthesia methods and their impact on neurocognitive outcomes and other complications in elderly patients undergoing hemiarthroplasty - Gengrui Zhong; Xiaoli Huang; Congye Li; Deqiang Wang; Dingding Huang; Menghan Sun; Quanhong Zhou; Yong Guo (Frontiers in Medicine)
ObjectiveTo evaluate the effects of various anesthesia techniques on perioperative neurocognitive disorders (PND) and other postoperative complications in elderly patients undergoing hemiarthroplasty for hip fractures.MethodsThis multicenter retrospective observational study analyzed 5,005 elderly patients (≥65 years) with hip fractures who underwent hemiarthroplasty and had complete perioperative clinical data. Patients were categorized into five anesthesia groups: a, Combined intravenous-inhalation anesthesia (IVA + IHA); b, IVA + IHA with peripheral nerve block (PNB); c, Intravenous anesthesia (IVA) with PNB; d, Spinal anesthesia (SA); e, SA with PNB. Postoperative delirium (POD) was assessed twice daily during the first 3 postoperative days using the Confusion Assessment Method (CAM). Delayed neurocognitive recovery (DNR) was evaluated via telephone follow-up on postoperative day 7. Other postoperative complications, as well as 30-day and 6-month mortality rates, were systematically recorded.ResultsThe analysis revealed no significant differences in POD incidence among the first three anesthesia groups (a/b/c) or between the last two groups (d/e) (p > 0.05). However, when comparing the combined first three groups with the combined last two groups, the difference was statistically significant (p < 0.05), with an overall p-value of 0.029. No significant differences were observed in DNR incidence among the five groups (p = 0.12), indicating that anesthesia methods significantly affected POD occurrence but not DNR. Significant differences were found in postoperative pulmonary infection (PI) rates among the five anesthesia groups (p = 0.0314). The overall PI incidence was significantly higher in general anesthesia groups compared to regional anesthesia groups, with notable differences in pairwise comparisons. However, no significant differences were observed in urinary tract infection (UTI), deep vein thrombosis (DVT), pulmonary thromboembolism (PTE), or mortality rates among the groups (p > 0.05). SA & SA + PNB (de) significantly reduced POD risk: SA: OR 0.3239 (95% CI 0.2215–0.4735), 67.61% risk reduction; SA + PNB: OR 0.3634 (95% CI 0.2966–0.4452), 63.66% risk reduction (Both statistically significant, CI excludes 1). IVA + IHA: OR 1.3929 (95% CI 1.0590–1.8320) suggested potential PI risk increase, but wider CI indicates lower certainty.ConclusionThese findings suggest that regional anesthesia may be associated with lower early POD and pulmonary infection rates. Further prospective randomized controlled trials are needed to validate these results.